Linguistic Landscape Analysis on Meal Advertisement and Its Potential as Authentic Materials In ELT - Nursaputri, Esamada Rose; Aisyah, Siti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Linguistic Landscape is an approach to study the language used by people in open spaces. Language in open spaces is very varied, starting from a variety of language choices, choices of shapes and colors, as well as language placement. Meal advertisements were chosen to be the subject of this research. This research aims to determine the potential of the linguistic landscape of a meal advertisement to be used as authentic material in English Language Teaching. The data used were advertisements displaying food products from restaurants and stalls in Surabaya, East Java, Indonesia. The data obtained are ten advertisements, which were processed qualitatively. The results show that the advertisements collected use English as their main language. These advertisements can be used as authentic material in ELT. However, after analysis, it is stated that teachers must be careful and pay attention to the characteristics of authentic material that is good for use in English classes.